Lithium ion adsorption material and preparation method and application thereof

Through the chemical bonding of the vinyl silane-modified lithium ion sieve to the polyvinyl chloride molecular chain and the vinyl monomer modification, the problem of insufficient stability and hydrophilicity of lithium adsorbent is solved, and high selectivity and stability are achieved. Adsorbing lithium ion materials, suitable for liquid lithium extraction applications of lithium batteries.

CN119186512AActive Publication Date: 2024-12-27CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310769641.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-27
Publication Date
2024-12-27
Estimated Expiration
2043-06-27

AI Technical Summary

Technical Problem

The existing lithium adsorbents have poor stability and insufficient hydrophilicity during long-term use, which can easily lead to the shedding and embedding of lithium ion sieves, affecting the adsorption-desorption performance.

Method used

The vinyl silane-modified lithium ion sieve is connected to the polyvinyl chloride molecular chain through chemical bonds to form an interpenetrating network structure, improving the compatibility and stability of the lithium ion sieve, and improving it through vinyl monomers containing electron-absorbing groups. The hydrophilicity of the material.

Benefits of technology

It improves the stability and selectivity of materials that adsorb lithium ions in long-term use, reduces the embedding of lithium ion sieves, enhances the adsorption desorption rate and anti-swelling performance, and maintains high adsorption capacity and selectivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119186512A_ABST
    Figure CN119186512A_ABST
Patent Text Reader

Abstract

The invention relates to the field of adsorption materials, and discloses a material for adsorbing lithium ions as well as a preparation method and application thereof. The material for adsorbing lithium ions comprises a polyvinyl chloride molecular chain and a polymer molecular chain A, wherein the polymer molecular chain A comprises a structural unit I from a vinyl monomer containing an electron withdrawing group and a structural unit II from a vinyl silane modified lithium ion sieve. According to the material for adsorbing the lithium ions, the vinyl silane modified lithium ion sieve can be connected with a polymer molecular chain forming a framework through a chemical bond, the lithium ion sieve is not prone to falling off in the long-term use process, the modified lithium ion sieve has excellent compatibility with polyvinyl chloride serving as the framework, and the service life of the material is prolonged. Therefore, the material for adsorbing lithium ions has excellent stability while maintaining high adsorption and desorption rate and selectivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of adsorption materials, and in particular to a material for adsorbing lithium ions, a preparation method thereof and an application thereof. Background Art

[0002] With the rapid development of the lithium battery industry, the demand for lithium resources in all walks of life is continuing to grow, and the importance of lithium production is also increasing. At present, lithium resources are mainly distributed in lithium ore and salt lake brine. However, lithium ore resources are constantly decreasing, and the cost of development is increasing. In contrast, lithium water resources in salt lake brine are low-cost and abundant in reserves. my country has abundant liquid lithium resources, but extracting lithium from lithium water resources is a challenging task. At present, the main methods for extracting lithium from salt lakes are adsorption, precipitation, extraction, electrodialysis, calcination, etc. Adsorption is one of the methods with simple process, green energy saving, good selectivity, and broad application prospects. However, there is often a problem of low lithium taste in salt lake brine, so the preparation of highly selective lithium adsorbents is the key. At present, highly selective lithium adsorbents mainly include ion sieve adsorbents and amorphous hydroxide adsorbents. However, since these adsorbents are in powder state after synthesis, they cannot be directly applied to conventional equipment such as fixed beds for adsorption-desorption lithium extraction. In order to improve the stability of the adsorbent, it is usually necessary to granulate the lithium adsorbent to obtain a granular material for adsorbing lithium ions. Currently, common granulation methods include the use of inorganic binders, natural polymer materials and organic polymer materials. However, these methods all have some defects, such as poor stability, poor hydrophilicity, and easy embedding of powdered adsorbents. Therefore, it is urgent to solve the problems of poor hydrophilicity of PVC-based granulated products, embedding of adsorbents, and decreased long-term cycle performance. Summary of the invention

[0003] The purpose of the present invention is to overcome the problems in the prior art that granulated products with polyvinyl chloride as a skeleton have poor selectivity and hydrophilicity and that a lithium ion sieve is easy to fall off during long-term use, resulting in poor stability. A material for adsorbing lithium ions and a preparation method and application thereof are provided. In the material for adsorbing lithium ions, a vinylsilane-modified lithium ion sieve can be connected to a polymer molecular chain forming a skeleton through a chemical bond. During long-term use, the lithium ion sieve is not easy to fall off, and the modified lithium ion sieve has excellent compatibility with the polyvinyl chloride as a skeleton, so that the material for adsorbing lithium ions has excellent stability while maintaining a high adsorption and desorption rate and selectivity.

[0004] In order to achieve the above object, the first aspect of the present invention provides a material for adsorbing lithium ions, wherein the material for adsorbing lithium ions comprises a polyvinyl chloride molecular chain and a polymer molecular chain A;

[0005] Wherein, the polymer molecular chain A comprises a structural unit I derived from a vinyl monomer containing an electron-withdrawing group and a structural unit II derived from a vinyl silane-modified lithium ion sieve.

[0006] A second aspect of the present invention provides a method for preparing a material for adsorbing lithium ions, wherein the preparation method comprises the following steps:

[0007] (1) using vinyl silane to modify the lithium ion sieve to obtain a vinyl silane-modified lithium ion sieve;

[0008] (2) mixing polyvinyl chloride, vinyl silane-modified lithium ion sieve, and a vinyl monomer containing an electron-withdrawing group with a first solvent to obtain a first mixed solution;

[0009] (3) mixing the initiator and the second solvent to obtain a second mixed solution;

[0010] (4) The first mixed solution is added dropwise to the second mixed solution to carry out a polymerization reaction to obtain a material that absorbs lithium ions.

[0011] The third aspect of the present invention provides a lithium ion adsorbing material obtained by the above preparation method.

[0012] A fourth aspect of the present invention provides an application of the above-mentioned lithium ion adsorbing material in lithium extraction.

[0013] Through the above technical solution, the lithium ion adsorbing material provided by the present invention and its preparation method and application can achieve the following beneficial effects:

[0014] In the lithium ion adsorbing material provided by the present invention, the vinyl silane modified lithium ion sieve can be connected to the polymer molecular chain forming the skeleton through chemical bonds. During long-term use, the lithium ion sieve is not easy to fall off, thereby improving the stability of the material for adsorbing lithium ions; and the vinyl silane modified lithium ion sieve has excellent compatibility with the polyvinyl chloride as the skeleton, so that the lithium ion sieve is uniformly dispersed in the polymer skeleton, reducing the embedding phenomenon of the lithium ion sieve in the lithium ion adsorbing material, so that the lithium ion adsorbing material has high adsorption and desorption rate, selectivity and stability.

[0015] Furthermore, in the lithium ion adsorbing material provided by the present invention, the polyvinyl chloride molecular chains and the polymer molecular chains A are entangled with each other to form an interpenetrating network structure, thereby making the internal pore penetration of the lithium ion adsorbing material high, which is beneficial to water mass transfer; and the structural unit containing the vinyl monomer containing the electron-withdrawing group contained in the lithium ion adsorbing material improves the hydrophilicity of the lithium ion adsorbing material, so that the lithium ion adsorbing material has excellent anti-swelling property in the salt solution, and at the same time increases the selectivity of the lithium ion adsorbing material for lithium ions. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 It is the SEM image of the cross-section of the material for adsorbing lithium ions in Example 1;

[0017] Figure 2 It is the SEM image of the cross-section of the material for adsorbing lithium ions in Comparative Example 2. Detailed implementation manners

[0018] In the ranges disclosed herein, the endpoints and any values are not limited to the exact ranges or values. These ranges or values should be understood to include values close to these ranges or values. For numerical ranges, between the endpoint values of each range, between the endpoint values of each range and individual point values, and between individual point values, they can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed herein.

[0019] To achieve the above object, a first aspect of the present invention provides a material for adsorbing lithium ions, characterized in that the material for adsorbing lithium ions includes a polyvinyl chloride molecular chain and a polymer molecular chain A;

[0020] Wherein, the polymer molecular chain A includes a structural unit I derived from a vinyl monomer containing an electron-withdrawing group and a structural unit II derived from a vinyl silane-modified lithium ion sieve.

[0021] In the present invention, in the material for adsorbing lithium ions, the vinyl silane-modified lithium ion sieve can be connected to the polymer molecular chain forming the backbone through chemical bonds. During long-term use, the lithium ion sieve is not easily detached, improving the stability of the material for adsorbing lithium ions; and the vinyl silane-modified lithium ion sieve has excellent compatibility with the polyvinyl chloride as the backbone, enabling the lithium ion sieve to be uniformly dispersed in the polymer backbone, reducing the embedding phenomenon of the lithium ion sieve in the material for adsorbing lithium ions, and making the material for adsorbing lithium ions have a high adsorption and desorption rate, selectivity, and stability.

[0022] According to the present invention, based on the total weight of the material for adsorbing lithium ions, the content of the polyvinyl chloride molecular chain is 12-58 wt%; the content of the structural unit I in the polymer molecular chain A is 0.7-14.5 wt%, and the content of the structural unit II in the polymer molecular chain A is 27-83.5 wt%.

[0023] In the present invention, the inventors have found through research that when the contents of the polyvinyl chloride molecular chain, the structural unit I, and the structural unit II in the polymer molecular chain A in the material for adsorbing lithium ions meet the above ranges, the material for adsorbing lithium ions has excellent hydrophilicity, excellent anti-swelling performance in salt solutions, and excellent adsorption capacity. At the same time, the material for adsorbing lithium ions has strong selectivity for lithium ions.

[0024] In the present invention, the sum of the content of the polyvinyl chloride molecular chain, the content of structural unit I in polymer molecular chain A, and the content of structural unit II in polymer molecular chain B is 100 wt%.

[0025] Further, based on the total weight of the lithium-ion adsorbing material, the content of the polyvinyl chloride molecular chain is 20 - 46 wt%; the content of structural unit I in polymer molecular chain A is 8 - 14 wt%; the content of structural unit II in polymer molecular chain A is 45 - 75 wt%.

[0026] According to the present invention, the electron-withdrawing group in the vinyl monomer containing an electron-withdrawing group is selected from at least one of a carboxyl group, a sulfate group, a sulfonic acid group, a boric acid group, and a sulfonamide group.

[0027] Further, the vinyl monomer containing an electron-withdrawing group is selected from at least one of acrylic acid, styrene sulfonic acid, vinyl sulfuric acid, (4 - ((2 - acrylamidoethyl)carbamoyl)-3 - fluorophenyl)boronic acid, 4-(3-(acryloyloxy)propoxy)benzoic acid, N-[(4 - sulfonamido)phenyl]acrylamide, 2 - acrylamido - 2 - methylpropanesulfonic acid, sodium 2 - methyl - 2 - [(1 - oxo - 2 - propenyl)amino]-1 - propanesulfonate, 5 - acrylamido - 2-(aminomethyl)phenylboronic acid, 2 - acrylamidophenylboronic acid, 5 - acrylamido - 2 - ((dimethylamino)methyl)phenylboronic acid, 1 - acryloylpiperidine - 4 - carboxylic acid, 6-(acryloyloxy)hexanoic acid, 4-(acrylamide)benzoic acid, and 4 - methacrylamidosalicylic acid. When the vinyl monomer containing an electron-withdrawing group is selected from the above specific types, the formed interpenetrating network structure improves the hydrophilicity of the lithium-ion adsorbing material, and at the same time, can significantly improve the selectivity of the lithium-ion adsorbing material for lithium ions. Particularly preferably, the vinyl monomer containing an electron-withdrawing group is acrylic acid.

[0028] According to the present invention, the vinyl silane is selected from at least one of vinyltriethoxysilane, vinyltrimethoxysilane, vinyltris(2 - methoxyethoxy)silane, vinyltriisopropoxysilane, methylvinyldimethoxysilane, and vinyltriacetoxysilane.

[0029] According to the present invention, the average particle size of the lithium-ion adsorbing material is 2 - 5 mm.

[0030] In the present invention, when the lithium-ion adsorbing material has the above specific average particle size, it can ensure that the lithium-ion adsorbing material has a high packing density when used for lithium extraction in a liquid environment, and ultimately improve the lithium adsorption capacity.

[0031] Further, the average particle size of the lithium-ion adsorbing material is 3 - 4 mm.

[0032] According to the present invention, the average pore diameter of the material for adsorbing lithium ions is 0.1 - 10 μm.

[0033] In the present invention, when the material for adsorbing lithium ions has the above - mentioned specific average pore diameter, the material for adsorbing lithium ions can have a high saturated adsorption capacity when used for extracting lithium from liquid.

[0034] Further, the average pore diameter of the material for adsorbing lithium ions is 3 - 6 μm.

[0035] In the present invention, both the average particle size and the average pore diameter of the material for adsorbing lithium ions are measured by a scanning electron microscope. Specifically, 10 observation points are randomly selected for scanning electron microscope testing, and the size of each observation area is not less than 500×500 μm, and the average value is calculated.

[0036] According to the present invention, the specific surface area of the material for adsorbing lithium ions is 10 - 200 m 2 / g.

[0037] In the present invention, when the material for adsorbing lithium ions has the above - mentioned specific surface area, the material for adsorbing lithium ions can have a high saturated adsorption capacity when used for extracting lithium from liquid.

[0038] Further, the specific surface area of the material for adsorbing lithium ions is 30 - 60 m 2 / g.

[0039] According to the present invention, the porosity of the material for adsorbing lithium ions is 40 - 60%.

[0040] In the present invention, when the material for adsorbing lithium ions has the above - mentioned specific porosity, the material for adsorbing lithium ions can have a high saturated adsorption capacity when used for extracting lithium from liquid.

[0041] Further, the porosity of the material for adsorbing lithium ions is 48 - 58%.

[0042] According to the present invention, the thickness of the coating layer formed by vinylsilane in the vinylsilane - modified lithium ion sieve is 2 - 8 nm.

[0043] In the present invention, when the thickness of the coating layer formed by vinylsilane in the vinylsilane - modified lithium ion sieve is controlled to meet the above range, it can ensure excellent compatibility between the lithium ion sieve and the polymer. Thus, the obtained vinylsilane - modified lithium ion sieve can be uniformly dispersed in the polymer skeleton, and the loading amount of the vinylsilane - modified lithium ion sieve in the polymer skeleton can be increased. And the specific surface area of the lithium ion sieve in the obtained material for adsorbing lithium ions is large, thereby improving the adsorption capacity of the material for adsorbing lithium ions.

[0044] Furthermore, the thickness of the coating layer formed by hydroxyl groups in the vinylsilane-modified lithium ion sieve is 3-5 nm.

[0045] In the present invention, the thickness of the coating layer formed by vinyl silane in the vinyl silane-modified lithium ion sieve is measured by TEM transmission electron microscope observation.

[0046] According to the present invention, the water content of the vinylsilane-modified lithium ion sieve is less than or equal to 0.5 wt %.

[0047] In the present invention, when the moisture content of the vinyl silane-modified lithium ion sieve is controlled to meet the above range, it is possible to avoid phase separation between the polymer and the vinyl silane-modified lithium ion sieve due to the presence of water, thereby causing the compatibility between the polymer molecular chain containing the vinyl silane-modified lithium ion sieve structural unit and the polyvinyl chloride molecular chain to deteriorate.

[0048] In the present invention, the water content of the hydroxyl-modified lithium ion sieve refers to the free water content in the hydroxyl-modified lithium ion sieve.

[0049] According to the present invention, the lithium ion sieve is selected from titanium-based lithium ion sieves and / or manganese-based ion sieves.

[0050] According to the present invention, the lithium ions are selected from LiMn2O4, Li 1.6 Mn 1.6 O4、Li 1.33 Mn 1.67 O4、Li4Mn5O 12 、LiMnO2、Li2TiO3、Li 1.33 Ti 1.66 O4 and Li4Ti5O 12 At least one of .

[0051] A second aspect of the present invention provides a method for preparing a material for adsorbing lithium ions, characterized in that the preparation method comprises the following steps:

[0052] (1) using vinyl silane to modify the lithium ion sieve to obtain a vinyl silane-modified lithium ion sieve;

[0053] (2) mixing polyvinyl chloride, vinyl silane-modified lithium ion sieve, a vinyl monomer containing an electron-withdrawing group and a first solvent to obtain a first mixed solution;

[0054] (3) mixing the initiator and the second solvent to obtain a second mixed solution;

[0055] (4) The first mixed solution is added dropwise to the second mixed solution to carry out a polymerization reaction, thereby obtaining a material that absorbs lithium ions.

[0056] In the present invention, in the presence of polyvinyl chloride, a lithium ion sieve modified by vinyl silane is polymerized with a vinyl monomer containing an electron-withdrawing group. While the vinyl silane-modified lithium ion sieve and the ethylene monomer containing the electron-withdrawing group are polymerized to form a polymer molecular chain, entanglement occurs with the polyvinyl chloride molecular chain to form a polymer skeleton with an interpenetrating network structure, so that the lithium ion sieve can be evenly dispersed between the polymer skeletons, and the lithium ion sieve and the skeleton are connected by chemical bonds. During long-term use, the lithium ion sieve is not easy to fall off, so that the prepared lithium ion adsorbing material has not only a high adsorption and desorption rate, but also high stability.

[0057] According to the present invention, the lithium ion sieve is selected from titanium-based lithium ion sieves and / or manganese-based ion sieves.

[0058] Furthermore, the lithium ion is selected from LiMn2O4, Li 1.6 Mn 1.6 O4、Li 1.33 Mn 1.67 O4、Li4Mn5O 12 、LiMnO2、Li2TiO3、Li 1.33 Ti 1.66 O4 and Li4Ti5O 12 At least one of .

[0059] In the present invention, the particle size of the lithium ion sieve is 0.05-500 μm.

[0060] According to the present invention, the vinyl silane is at least one selected from vinyl triethoxysilane, vinyl trimethoxysilane, vinyl tri(2-methoxyethoxy)silane, vinyl triisopropoxysilane, methyl vinyl dimethoxysilane, and vinyl triacetoxysilane.

[0061] According to the present invention, the mass ratio of the lithium ion sieve to the vinyl silane is 1:1.8-3.2.

[0062] In the present invention, when the weight ratio of vinyl silane to lithium ion sieve is controlled to meet the above range, it can be ensured that the prepared vinyl silane-modified lithium ion sieve contains sufficient reactive groups that can react with the vinyl monomer containing the electron-withdrawing group, thereby efficiently forming an interpenetrating network structure between the polyvinyl chloride molecular chains and the polymer molecular chains, and at the same time significantly improving the hydrophilicity of the material that adsorbs lithium ions.

[0063] Furthermore, the mass ratio of the lithium ion sieve to the vinyl silane is 1:1.8-2.2.

[0064] According to the present invention, the modification is carried out under acidic conditions. Preferably, the modification conditions include: modification temperature of 60-80° C., modification time of 2-6 h, and pH value of 1-3.

[0065] In the present invention, the modification further comprises ball milling and drying the modified product. Preferably, in the present invention, the ball milling and drying make the water content of the vinylsilane modified lithium ion sieve less than or equal to 0.5wt%.

[0066] In the present invention, when the moisture content of the vinyl silane-modified lithium ion sieve is controlled to meet the above range, it is possible to avoid phase separation between the polymer and the vinyl silane-modified lithium ion sieve due to the presence of water, thereby causing the compatibility between the polymer molecular chain containing the vinyl silane-modified lithium ion sieve structural unit and the polyvinyl chloride molecular chain to deteriorate.

[0067] In the present invention, the water content of the hydroxyl-modified lithium ion sieve refers to the free water content in the hydroxyl-modified lithium ion sieve.

[0068] According to the present invention, the thickness of the coating layer formed by vinyl silane in the vinyl silane-modified lithium ion sieve is 2-8 nm.

[0069] In the present invention, when the thickness of the coating layer formed by vinyl silane in the vinyl silane-modified lithium ion sieve is controlled to meet the above range, it is possible to ensure that the lithium ion sieve has excellent compatibility with the polymer, and the vinyl silane-modified lithium ion sieve obtained thereby can be evenly dispersed in the polymer skeleton, and the loading amount of the vinyl silane-modified lithium ion sieve in the polymer skeleton is increased, and the lithium ion sieve in the lithium ion adsorbing material thus obtained has a high specific surface area, thereby increasing the adsorption capacity of the lithium ion adsorbing material.

[0070] Furthermore, the thickness of the coating layer formed by hydroxyl groups in the vinylsilane-modified lithium ion sieve is 3-5 nm.

[0071] According to the present invention, the weight average molecular weight of the polyvinyl chloride is 50,000-110,000 g / mol.

[0072] In the present invention, the polyvinyl chloride having the above-mentioned specific weight average molecular weight is used, which is easier to form an interpenetrating network structure with the polymer molecular chain A comprising a vinyl silane-modified lithium ion sieve structural unit and a vinyl monomer structural unit containing an electron-withdrawing group.

[0073] According to the present invention, the electron-withdrawing group in the electron-withdrawing group-containing vinyl monomer is selected from at least one of a carboxyl group, a sulfate group, a sulfonic acid group, a boric acid group and a sulfonamide group.

[0074] According to the present invention, the vinyl monomer containing an electron-withdrawing group is selected from at least one of acrylic acid, styrene sulfonic acid, vinyl sulfuric acid, (4-((2-acrylamidoethyl)aminoformyl)-3-fluorophenyl)boric acid, 4-(3-(acryloyloxy)propoxy)benzoic acid, N-[(4-sulfonamide)phenyl]acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, 2-methyl-2-[(1-oxo-2-propenyl)amino]-1-propanesulfonic acid sodium salt, 5-acrylamide-2-(aminomethyl)phenylboric acid, 2-acrylamidephenylboric acid, 5-acrylamide-2-((dimethylamino)methyl)phenylboric acid, 1-acryloylpiperidine-4-carboxylic acid, 6-(acryloyloxy)hexanoic acid, 4-(acrylamide)benzoic acid and 4-methacrylamidosalicylic acid; preferably acrylic acid.

[0075] According to the present invention, the first solvent is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide.

[0076] In the present invention, there is no particular limitation on the amount of the first solvent, as long as the polyvinyl chloride, the vinyl silane-modified lithium ion sieve and the vinyl monomer containing the electron-withdrawing group can be fully mixed.

[0077] According to the present invention, based on the total weight of the polyvinyl chloride, the vinyl silane-modified lithium ion sieve and the vinyl monomer containing an electron-withdrawing group, the amount of the polyvinyl chloride is 12-58wt%, the amount of the vinyl silane-modified lithium ion sieve is 0.7-14.5wt%, and the amount of the vinyl monomer containing an electron-withdrawing group is 27-83.5wt%.

[0078] In the present invention, when the amounts of polyvinyl chloride, vinyl silane-modified lithium ion sieve and vinyl monomer containing electron-withdrawing groups are controlled to meet the above ranges, the obtained lithium ion adsorbing material can have excellent hydrophilicity, excellent anti-swelling properties in salt solutions, and excellent adsorption capacity.

[0079] Furthermore, based on the total weight of the polyvinyl chloride, the vinyl silane-modified lithium ion sieve and the vinyl monomer containing an electron-withdrawing group, the amount of the polyvinyl chloride is 20-46wt%, the amount of the vinyl silane-modified lithium ion sieve is 8-14wt%, and the amount of the vinyl monomer containing an electron-withdrawing group is 45-75wt%.

[0080] In the present invention, there is no particular limitation on the mixing conditions in step (2), as long as the polyvinyl chloride, vinyl silane-modified lithium ion sieve and the vinyl monomer containing the electron-withdrawing group are evenly mixed. For example, the mixing conditions include: a mixing temperature of 30-70°C, preferably 30-50°C.

[0081] According to the present invention, the initiator is selected from at least one of potassium persulfate, ammonium persulfate and azobisisobutyronitrile.

[0082] According to the present invention, the amount of the initiator is 1-14 wt % based on the total amount of the vinyl silane-modified lithium ion sieve and the vinyl monomer containing the electron-withdrawing group.

[0083] In the present invention, when the amount of the initiator is controlled to meet the above range, the vinylsilane-modified lithium ion sieve and the ethylene monomer containing the electron-withdrawing group can have a suitable polymerization rate, thereby controlling the polyvinyl chloride molecular chain and the polymer molecular chain A to form an interpenetrating network structure at a suitable rate.

[0084] According to the present invention, the dropping speed is 1-5 mL / min.

[0085] In the present invention, when the speed of dripping the first mixed liquid into the second mixed liquid is controlled to meet the above range, the vinyl silane-modified lithium ion sieve and the ethylene monomer containing the electron-withdrawing group can have a suitable polymerization rate, thereby controlling the polyvinyl chloride molecular chain and the polymer molecular chain A to form an interpenetrating network structure at a suitable rate.

[0086] Furthermore, the dropping speed is 2-3 mL / min.

[0087] According to the present invention, the conditions of the polymerization reaction include: a polymerization temperature of 30-75° C. and a polymerization time of 2-12 h.

[0088] According to the present invention, the method further comprises: a step of washing the material that absorbs lithium ions with an acidic solution.

[0089] In the present invention, the material for adsorbing lithium ions is a precursor of the material for adsorbing lithium ions, and the material for adsorbing lithium ions is washed with an acidic solution so that the Li + and H + Exchange to activate the precursor and obtain H-type lithium ion sieve, such as Li 1.33 Mn 1.67 O4 to H 1.33 Mn 1.67 O4. H-type lithium ion sieve has a specific adsorption effect on lithium ions.

[0090] According to the present invention, under the action of a peristaltic pump, an acidic solution is used to circulate and wash the material that absorbs lithium ions.

[0091] Furthermore, the acidic solution is selected from at least one of hydrochloric acid, phosphoric acid and sulfuric acid.

[0092] Furthermore, the concentration of the acidic solution is 0.1-1 mol / L.

[0093] Furthermore, the flow rate of the peristaltic pump is 1-6 BV / h, and the cycle time is 1-24h.

[0094] In the present invention, when the circulating washing conditions or the concentration of the acidic solution are controlled to meet the above range, the ion exchange can be ensured without destroying the structure of the ion sieve.

[0095] In a specific embodiment of the present invention, the concentration of the acidic solution is 0.1-0.6 mol / L; the flow rate of the peristaltic pump is 2-5 BV / h, and the circulation time is 4-24 h.

[0096] The third aspect of the present invention provides a lithium ion adsorbing material prepared by the above method.

[0097] A fourth aspect of the present invention provides an application of the above-mentioned lithium ion adsorbing material in lithium extraction, preferably in a liquid environment.

[0098] The present invention will be described in detail below through examples.

[0099] Take the adsorbent materials prepared in the examples and comparative examples and perform the following measurements respectively:

[0100] The moisture content of vinylsilane modified lithium ion sieve was measured using a moisture meter.

[0101] The porosity of the material for adsorbing lithium ions was measured by a mercury intrusion instrument AutoPore IV 9500 (Micromeritics Instruments, Inc., USA).

[0102] The average pore size and average particle size of the material for adsorbing lithium ions were tested by scanning electron microscopy.

[0103] The morphology of the materials adsorbing lithium ions was characterized by scanning electron microscopy (SEM, S-4800, Japan).

[0104] The specific surface area of ​​the material that adsorbs lithium ions is determined by the BET method. The specific method is to measure the adsorption-desorption isotherm of the material that adsorbs lithium ions to N2 at 77K, and obtain the BET specific surface area by fitting.

[0105] The contents of polyvinyl chloride molecular chains and polymer molecular chains A in the material for adsorbing lithium ions, and the contents of structural units I and II in polymer molecular chain A are obtained by measuring the contents of elements using X-ray photoelectron spectroscopy (XPS), wherein the content of the polyvinyl chloride molecular chain is obtained from the content of the Cl element, the content of the structural unit II is obtained from the content of the metal Mn or Ti, and the rest is the content of the structural unit I.

[0106] The content of vinylsilane in vinylsilane-modified lithium ion sieve was measured by weight gain method.

[0107] Adsorption-desorption cycle: The obtained material particles (4 g) adsorbing lithium ions are loaded into a glass column for acid washing, and 0.5 M hydrochloric acid (200 mL) is pumped in at a flow rate of 2BV / h by a peristaltic pump for 24 hours to wash and remove lithium ions in the particles. Then, after washing with deionized water until neutral, a mixture of lithium chloride and magnesium chloride (lithium ion content 100 mg / L, magnesium ion concentration 20000 mg / L, ammonia water adjusted to pH = 9.5, V = 400 mL) is pumped in at a flow rate of 2 mL / min by a peristaltic pump for dynamic adsorption-desorption cycle adsorption for 24 hours. Then, 0.5 M hydrochloric acid (200 mL) is pumped in at a flow rate of 2 mL / min by a peristaltic pump for 24 hours to desorb lithium ions in the particles. Then, washing with deionized water until neutral is one cycle. One adsorption-desorption cycle monitors the change of adsorption capacity over time and calculates the saturated adsorption capacity Q, and the calculation formula is as follows:

[0108]

[0109] Wherein, Q is the saturated adsorption capacity, in mg / g, reflecting the adsorption amount when the adsorption reaches equilibrium; C0 and C are the ion concentrations in the solution at the start and at the saturation of adsorption, in mg / L, respectively; V is the volume of the adsorption solution, in L; m is the mass of the material particles that adsorb lithium ions, in g. Ion chromatography (ICS-1100, DIONEX, America) was used to measure the ion concentration.

[0110] The adsorption capacity decrease rate after 30 cycles of operation is calculated according to the following formula:

[0111] The percentage of adsorption capacity decrease after 30 cycles of operation = (Q1-Q30) / Q1*100%, Q1 is the first adsorption capacity, Q30 is the 30th adsorption capacity.

[0112] Partition coefficient (K d ), in mg / L, reflects the affinity of the material particles that adsorb lithium ions for ions.

[0113] Selectivity coefficient It refers to the preference of the adsorbent for ions A when adsorbing ions A and B. The larger the value, the better the selectivity for A. It reflects the selectivity of the material particles adsorbing lithium ions for different ions. It is the distribution coefficient of the two ions (K d ) ratio.

[0114]

[0115]

[0116] In the above formula, C0 is the concentration of each ion in the solution before adsorption, mg / L; C e is the concentration of each ion when adsorption is saturated, mg / L; V is the volume of the solution, mL; m is the mass of the material particles that adsorb lithium ions, g. K A is the distribution coefficient K of ion A B is the distribution coefficient of B ion.

[0117] The swelling performance of the material that absorbs lithium ions is measured by the volume swelling rate of the material that absorbs lithium ions in high salt water.

[0118] The volume swelling rate P is determined by placing lithium ion adsorbing material particles with a volume of V0 in sufficient high-salt water (lithium ion content 100 mg / L, magnesium ion concentration 20000 mg / L) at 25°C. After 24 hours, the volume V1 is taken out and measured, P = (V1-V0) / V0×100%.

[0119] The hydrophilicity is expressed by the amount of pure water absorbed by the material that adsorbs lithium ions. The specific method is: at 25°C, place a unit mass of material particles that adsorb lithium ions in sufficient distilled water, and measure the amount of water adsorbed when the mass of the material that adsorbs lithium ions no longer increases, in units of g / g.

[0120] In addition, in the following examples and comparative examples, all reagents were purchased from J&K Technology Co., Ltd.

[0121] Example 1

[0122] (1) Take lithium ion screen Li 1.6 Mn 1.6 O4 (particle size 1 μm) was dispersed by a homogenizer and added to a vinyl triethoxysilane aqueous solution (pH adjusted to 1 with hydrochloric acid) to make the mass ratio of lithium ion sieve to vinyl triethoxysilane 1:1.8, and stirred at 80°C for 2 hours. The solution was then centrifuged and the solid phase material was dried to obtain a vinyl silane-modified lithium ion sieve with a water content of 0.2wt%.

[0123] (2) Weigh 10 g of polyvinyl chloride (molecular weight 50,000 g / mol), 2.3 g of acrylic acid, and 10 g of the vinylsilane-modified lithium ion sieve prepared in step (1) and add them to 87.7 g of DMF. Place the mixture in a 500 mL beaker and heat to 60° C. with stirring. After dissolution, cool the mixture to 30° C. to obtain a first mixed solution for later use.

[0124] (3) Weigh 1 g of ammonium persulfate and dissolve it in 100 mL of water to obtain a second mixed solution. Add the first mixed solution to the second mixed solution at a dropping speed of 1 mL / min and react at 30° C. for 12 h to obtain material particles A1 that adsorb lithium ions.

[0125] Example 2

[0126] (1) Take lithium ion screen Li 1.6 Mn 1.6 O4 (particle size 1 μm) was dispersed by a homogenizer and added to a vinyl triethoxysilane aqueous solution (pH adjusted to 2 with hydrochloric acid) to make the mass ratio of lithium ion sieve and vinyl triethoxysilane 1:3.6, and stirred at 60°C for 4 hours. The solution was then centrifuged and the solid phase material was dried to obtain a vinyl silane-modified lithium ion sieve with a water content of 0.2wt%.

[0127] (2) Weigh 10 g of polyvinyl chloride (molecular weight 50,000 g / mol) powder, 2.3 g of acrylic acid, and 5 g of the vinylsilane-modified lithium ion sieve prepared in step (1), add 87.7 g of DMF, place in a 500 mL beaker, and heat to 60° C. with stirring. After dissolving, cool to 30° C. to obtain a first mixed solution for use.

[0128] (3) Weigh 1 g of ammonium persulfate and dissolve it in 100 mL of water to obtain a second mixed solution. Add the first mixed solution dropwise to the second mixed solution at a dropping speed of 1 mL / min and react at 35° C. for 2 h to obtain material particles A2 that adsorb lithium ions.

[0129] Example 3

[0130] (1) Take lithium ion screen Li 1.6 Mn 1.6 O4 (particle size 1 μm) was dispersed by a homogenizer and added to a vinyl triethoxysilane aqueous solution (pH adjusted to 3 with hydrochloric acid) to make the mass ratio of lithium ion sieve and vinyl triethoxysilane 1:2, and stirred at 80°C for 2 hours. The solution was then centrifuged and the solid phase material was dried to obtain a vinyl silane-modified lithium ion sieve with a water content of 0.2wt%.

[0131] (2) Weigh 6 g of polyvinyl chloride (molecular weight 50,000 g / mol) powder, 4.3 g of acrylic acid, and 20 g of the vinylsilane-modified lithium ion sieve obtained in step (1), add 89.7 g of DMF, place in a 500 mL beaker, heat to 60° C. with stirring, and cool to 30° C. after dissolution to obtain a first mixed solution for use.

[0132] (3) Weigh 1 g of ammonium persulfate and dissolve it in 100 mL of water to obtain a second mixed solution. Add the first mixed solution to the second mixed solution at a dropping speed of 1 mL / min and react at 40° C. for 8 h to obtain material particles A3 that adsorb lithium ions.

[0133] Example 4

[0134] (1) Take lithium ion screen Li 1.6 Mn 1.6O4 (particle size 1 μm) was dispersed by a homogenizer and added to a vinyl triethoxysilane aqueous solution (pH adjusted to 2 with hydrochloric acid) to make the mass ratio of lithium ion sieve and vinyl triethoxysilane 1:2, and stirred at 80°C for 2 hours. The solution was then centrifuged and the solid phase material was dried to obtain a vinyl silane-modified lithium ion sieve with a water content of 0.2wt%.

[0135] (2) Weigh 6 g of polyvinyl chloride (molecular weight 50,000 g / mol), 2.3 g of acrylic acid, and 40 g of the vinylsilane-modified lithium ion sieve prepared in step (1), add 91.7 g of DMF, place in a 500 mL beaker, heat to 60° C. with stirring, and cool to 30° C. after dissolution to obtain a first mixed solution for use.

[0136] (3) Weigh 1 g of ammonium persulfate and dissolve it in 100 mL of water to obtain a second mixed solution. Add the first mixed solution to the second mixed solution at a dropping speed of 1 mL / min and react at 30° C. for 6 h to obtain material particles A4 that adsorb lithium ions.

[0137] Example 5

[0138] (1) Take lithium ion screen Li 1.6 Mn 1.6 O4 (particle size 1 μm) was dispersed by a homogenizer and added to a vinyl triethoxysilane aqueous solution (pH adjusted to 2 with hydrochloric acid) to make the mass ratio of lithium ion sieve and vinyl triethoxysilane 1:2, and stirred at 80°C for 2 hours. The solution was then centrifuged and the solid phase material was dried to obtain a vinyl silane-modified lithium ion sieve with a water content of 0.2wt%.

[0139] (2) Weigh 6 g of polyvinyl chloride (molecular weight 50,000 g / mol) powder, 0.22 g of acrylic acid, and 20 g of the vinylsilane-modified lithium ion sieve prepared in step (1), add 93.78 g of DMF, place in a 500 mL beaker, and heat to 60° C. with stirring. After dissolving, cool to 30° C. to obtain a first mixed solution for use.

[0140] (3) Weigh 1 g of ammonium persulfate and dissolve it in 100 mL of water to obtain a second mixed solution. Add the first mixed solution dropwise to the second mixed solution at a dropping speed of 1 mL / min, and react at 30° C. for 4 h to obtain a material A5 that absorbs lithium ions.

[0141] Example 6

[0142] The material for adsorbing lithium ions was prepared according to the method of Example 1, except that the acrylic acid in step (2) was replaced with an equal mass of styrene sulfonic acid to obtain the material A6 for adsorbing lithium ions.

[0143] Example 7

[0144] The material for adsorbing lithium ions was prepared according to the method of Example 1, except that the acrylic acid in step (2) was replaced with an equal mass of 1-acryloylpiperidine-4-carboxylic acid to obtain the material A7 for adsorbing lithium ions.

[0145] Example 8

[0146] The material for adsorbing lithium ions was prepared according to the method of Example 1, except that the vinyl triethoxysilane in step (1) was replaced with an equal mass of vinyl tri(2-methoxyethoxy)silane to obtain the material A8 for adsorbing lithium ions.

[0147] Example 9

[0148] The lithium ion absorbing material was prepared according to the method of Example 1, except that the vinyl triethoxysilane in step (1) was replaced with an equal mass of vinyl trimethoxysilane to obtain the lithium ion absorbing material A9.

[0149] Example 10

[0150] The material for adsorbing lithium ions was prepared according to the method of Example 1, except that the lithium ion sieve Li in step (1) was 1.6 Mn 1.6 O4 was replaced by an equal mass of lithium ion sieve Li2TiO3 (particle size 0.5 μm), and the material A10 for adsorbing lithium ions was obtained.

[0151] Embodiment 11

[0152] The material for adsorbing lithium ions was prepared according to the method of Example 1, except that the polyvinyl chloride in step (2) was replaced with polyvinyl chloride of the same mass and molecular weight of 80,000 g / mol to obtain the material A11 for adsorbing lithium ions.

[0153] Example 12

[0154] (1) Same as Example 1;

[0155] (2) Weigh 2.3 g of acrylic acid, 10 g of the vinylsilane-modified lithium ion sieve prepared in step (1), and 1 g of ammonium persulfate and dissolve them in 100 mL of water. After 30 min, centrifuge and dry the mixture to obtain a solid.

[0156] (3) Then, the obtained solid and 10 g of polyvinyl chloride (molecular weight 50,000 g / mol) were added to 87.7 g of DMF, placed in a 500 mL beaker, heated to 60° C. with stirring, dissolved, and cooled to 30° C. to obtain a first mixed solution for use. The first mixed solution was added dropwise to pure water at a dropping speed of 1 mL / min to obtain material particles A12 for adsorbing lithium ions.

[0157] Comparative Example 1

[0158] The same as Example 1, without the modification of step (1), to obtain material particles D1 for adsorbing lithium ions.

[0159] Comparative Example 2

[0160] The same as in Example 1, except that the modification in step (1) is not performed and acrylic acid is not added in step (2), to obtain a material D2 for adsorbing lithium ions.

[0161] Comparative Example 3

[0162] The same as in Example 1, except that the alkenyl triethoxysilane in step (1) was replaced with an equal amount of γ-aminopropyl triethoxysilane to obtain a material D3 for adsorbing lithium ions.

[0163] The lithium ion adsorbing materials prepared in the embodiments and comparative examples were tested, and the contents of the polyvinyl chloride molecular chain, the structural unit I of the vinyl monomer containing an electron-withdrawing group, and the structural unit II of the vinyl silane-modified lithium ion sieve in the lithium ion adsorbing materials, and the thickness of the coating layer formed by vinyl silane in the vinyl silane-modified lithium ion sieve are shown in Table 1.

[0164] The average particle size, average pore size, porosity and specific surface area of ​​the material for adsorbing lithium ions are shown in Table 2.

[0165] Table 1

[0166] PVC / wt% Structural unit I / wt% Structural unit II / wt% Average thickness of coating layer nm Example 1 45.5 9 45.5 3.2 Example 2 57.8 13.3 28.9 6.1 Example 3 20.3 13.2 66.5 3.3 Example 4 13.2 4.1 82.7 2.1 Example 5 23 10.2 66.8 3.4 Example 6 45.4 9.2 45.4 2.2 Example 7 45.6 9.1 45.3 2.2 Example 8 45.7 9.2 45.1 2.5 Example 9 45.2 9.1 45.7 5.1 Example 10 45.4 9 45.6 2.8 Embodiment 11 45.1 9.2 45.7 2.7 Example 12 45.5 9 45.5 2.7 Comparative Example 1 45.4 9.2 45.4 0 Comparative Example 2 48.9 0 51.1 0 Comparative Example 3 45.5 9 45.5 0.2

[0167] Table 2

[0168] Average particle size / mm Average pore size / μm Porosity / % <![CDATA[Specific surface area / m 2 / g]]> Example 1 3.5 3.8 58 41 Example 2 3.5 2.1 45 21 Example 3 3.5 4 57 37 Example 4 3.5 7.3 60 78 Example 5 3.5 3.9 48 32 Example 6 3.5 2.7 39 30 Example 7 3.5 2.6 31 21 Example 8 3.5 2.2 39 28 Example 9 3.5 6.9 36 26 Example 10 3.5 6.4 34 22 Embodiment 11 3.5 6.5 32 25 Example 12 3.4 0.12 32 11.2 Comparative Example 1 3.5 0.05 22 10 Comparative Example 2 3.2 0.01 18 8.9 Comparative Example 3 3.5 0.03 19 6.6

[0169] Test Case

[0170] The time required for the adsorption capacity of the material to adsorb lithium ions to reach 90% T 90% The adsorption capacity, saturated adsorption capacity, magnesium-lithium selectivity coefficient, volume swelling rate and hydrophilicity after 30 cycles of operation were tested, and the results are shown in Table 3.

[0171] Table 3

[0172]

[0173]

[0174] It can be seen from Table 1, Table 2 and Table 3 that, compared with Comparative Examples 1-3, the lithium ion adsorbing material prepared in Example 1-12 includes a polyethylene molecular chain and a polymer molecular chain A comprising a structural unit of a vinyl monomer from an electron-withdrawing group and a structural unit from a vinyl silane-modified lithium ion sieve, and an interpenetrating network structure is formed in situ between the polyethylene molecular chain and the polymer molecular chain A, so that the lithium ion sieve is evenly dispersed in the polymer skeleton, and the embedding phenomenon of the lithium ion sieve in the lithium ion adsorbing material is reduced. When the lithium ion adsorbing material is used for liquid lithium extraction, it has high saturated adsorption capacity, anti-swelling property, magnesium-lithium selectivity coefficient and hydrophilicity, and after 30 cycles of operation, it can still maintain a high adsorption capacity and has an excellent service life.

[0175] Figure 1 is a SEM image of the lithium ion adsorbing material of Example 1, Figure 1 It can be seen that the pores in the lithium ion adsorbing material A1 are highly connected and developed, with a filamentous network structure; the powder has no obvious agglomeration.

[0176] Figure 2 is a SEM image of the lithium ion adsorbing material of Comparative Example 2, Figure 2 It can be seen that the powder of the material D2 that adsorbs lithium ions is agglomerated in large quantities, has no through holes and the holes are blocked.

[0177] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A material for adsorbing lithium ions, characterized in that: The material for adsorbing lithium ions includes polyvinyl chloride molecular chains and polymer molecular chains A; The polymer molecular chain A comprises a structural unit I derived from a vinyl monomer containing an electron-withdrawing group and a structural unit II derived from a vinyl silane-modified lithium ion sieve.

2. The lithium ion adsorbing material according to claim 1, wherein: Based on the total weight of the lithium ion adsorbing material, the content of the polyvinyl chloride molecular chain is 12-58wt%; the content of the structural unit I in the polymer molecular chain A is 0.7-14.5wt%; the content of the structural unit II in the polymer molecular chain A is 27-83.5wt%; Preferably, based on the total weight of the material for adsorbing lithium ions, the content of the polyvinyl chloride molecular chain is 20-46wt%; the content of the structural unit I in the polymer molecular chain A is 8-14wt%; and the content of the structural unit II in the polymer molecular chain A is 45-75wt%.

3. The lithium ion adsorbing material according to claim 1 or 2, wherein: The electron-withdrawing group in the electron-withdrawing group-containing vinyl monomer is selected from at least one of a carboxyl group, a sulfate group, a sulfonic acid group, a boric acid group and a sulfonamide group; Preferably, the vinyl monomer containing an electron-withdrawing group is selected from at least one of acrylic acid, styrene sulfonic acid, vinyl sulfuric acid, (4-((2-acrylamidoethyl)carbamoyl)-3-fluorophenyl)boric acid, 4-(3-(acryloyloxy)propoxy)benzoic acid, N-[(4-sulfonamide)phenyl]acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, 2-methyl-2-[(1-oxo-2-propenyl)amino]-1-propanesulfonic acid sodium salt, 5-acrylamido-2-(aminomethyl)phenylboric acid, 2-acrylamidophenylboric acid, 5-acrylamido-2-((dimethylamino)methyl)phenylboric acid, 1-acryloylpiperidine-4-carboxylic acid, 6-(acryloyloxy)hexanoic acid, 4-(acrylamido)benzoic acid and 4-methacrylamidosalicylic acid; preferably acrylic acid; Preferably, the vinyl silane is at least one selected from vinyl triethoxysilane, vinyl trimethoxysilane, vinyl tri(2-methoxyethoxy)silane, vinyl triisopropoxysilane, methyl vinyl dimethoxysilane, and vinyl triacetoxysilane.

4. The lithium ion adsorbing material according to any one of claims 1 to 3, wherein: The average particle size of the material for adsorbing lithium ions is 2-5 mm, preferably 3-4 mm; Preferably, the average pore size of the lithium ion adsorbing material is 0.1-10 μm, preferably 3-6 μm; Preferably, the specific surface area of ​​the material for adsorbing lithium ions is 10-200 m 2 / g, preferably 30-60m 2 / g; Preferably, the porosity of the material for adsorbing lithium ions is 40-60%, preferably 48-58%.

5. The lithium ion adsorbing material according to any one of claims 1 to 4, wherein: The thickness of the coating layer formed by vinyl silane in the vinyl silane-modified lithium ion sieve is 2-8 nm, preferably 3-5 nm; Preferably, the water content of the vinylsilane-modified lithium ion sieve is less than or equal to 0.5wt%; Preferably, the lithium ion sieve is selected from titanium-based lithium ion sieves and / or manganese-based ion sieves; Preferably, the lithium ion is selected from LiMn2O4, Li 1.6 Mn 1.6 O4、Li 1.33 Mn 1.67 O4、Li4Mn5O 12 、LiMnO2、Li2TiO3、Li 1.33 Ti 1.66 O4 and Li4Ti5O 12 At least one of .

6. A method for preparing a material for adsorbing lithium ions, characterized in that: The preparation method comprises the following steps: (1) using vinyl silane to modify the lithium ion sieve to obtain a vinyl silane-modified lithium ion sieve; (2) mixing polyvinyl chloride, vinyl silane-modified lithium ion sieve, and a vinyl monomer containing an electron-withdrawing group with a first solvent to obtain a first mixed solution; (3) mixing the initiator and the second solvent to obtain a second mixed solution; (4) The first mixed solution is added dropwise to the second mixed solution to carry out a polymerization reaction, thereby obtaining a material that absorbs lithium ions.

7. The preparation method according to claim 6, wherein: The lithium ion sieve is selected from titanium-based lithium ion sieves and / or manganese-based ion sieves; Preferably, the lithium ion is selected from LiMn2O4, Li 1.6 Mn 1.6 O4、Li 1.33 Mn 1.67 O4、Li4Mn5O 12 、LiMnO2、Li2TiO3、Li 1.33 Ti 1.66 O4 and Li4Ti5O 12 At least one of; Preferably, the vinyl silane is selected from at least one of vinyl triethoxysilane, vinyl trimethoxysilane, vinyl tri(2-methoxyethoxy)silane, vinyl triisopropoxysilane, methyl vinyl dimethoxysilane, and vinyl triacetoxysilane; Preferably, the mass ratio of the lithium ion sieve to the vinyl silane is 1:1.8-3.2, preferably 1:1.8-2.2; Preferably, the modification conditions include: modification temperature of 60-80°C, modification time of 2-6h, pH value of 1-3; Preferably, the water content of the vinylsilane-modified lithium ion sieve is less than or equal to 0.5wt%; Preferably, the thickness of the coating layer formed by vinyl silane in the vinyl silane-modified lithium ion sieve is 2-8 nm, preferably 3-5 nm.

8. The preparation method according to claim 6 or 7, wherein: The weight average molecular weight of the polyvinyl chloride is 50,000-110,000 g / mol; Preferably, the electron-withdrawing group in the electron-withdrawing group-containing vinyl monomer is selected from at least one of a carboxyl group, a sulfate group, a sulfonic acid group, a boric acid group and a sulfonamide group; Preferably, the vinyl monomer containing an electron-withdrawing group is selected from at least one of acrylic acid, styrene sulfonic acid, vinyl sulfuric acid, (4-((2-acrylamidoethyl)carbamoyl)-3-fluorophenyl)boric acid, 4-(3-(acryloyloxy)propoxy)benzoic acid, N-[(4-sulfonamide)phenyl]acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, 2-methyl-2-[(1-oxo-2-propenyl)amino]-1-propanesulfonic acid sodium salt, 5-acrylamido-2-(aminomethyl)phenylboric acid, 2-acrylamidophenylboric acid, 5-acrylamido-2-((dimethylamino)methyl)phenylboric acid, 1-acryloylpiperidine-4-carboxylic acid, 6-(acryloyloxy)hexanoic acid, 4-(acrylamido)benzoic acid and 4-methacrylamidosalicylic acid; preferably acrylic acid; Preferably, the first solvent is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide; Preferably, based on the total weight of the polyvinyl chloride, the vinyl silane-modified lithium ion sieve and the vinyl monomer containing an electron-withdrawing group, the amount of the polyvinyl chloride is 12-58wt%, the amount of the vinyl silane-modified lithium ion sieve is 0.7-14.5wt%, and the amount of the vinyl monomer containing an electron-withdrawing group is 27-83.5wt%.

9. The preparation method according to any one of claims 6 to 8, wherein: The initiator is selected from at least one of potassium persulfate, ammonium persulfate and azobisisobutyronitrile; Preferably, the amount of the initiator is 1-14 wt % based on the total amount of the vinylsilane-modified lithium ion sieve and the vinyl monomer containing the electron-withdrawing group.

10. The preparation method according to any one of claims 6 to 9, wherein: The dropping speed is 1-5 mL / min, preferably 2-3 mL / min; Preferably, the polymerization reaction conditions include: polymerization temperature of 30-75° C., and polymerization time of 2-12 h.

11. The preparation method according to any one of claims 6 to 10, wherein: The method further comprises: washing the material adsorbing lithium ions with an acidic solution; Preferably, under the action of a peristaltic pump, an acidic solution is used to circulate and wash the material that absorbs lithium ions; Preferably, the acidic solution is selected from at least one of hydrochloric acid, phosphoric acid and sulfuric acid; Preferably, the concentration of the acidic solution is 0.1-1 mol / L; Preferably, the flow rate of the peristaltic pump is 1-6 BV / h, and the cycle time is 1-24 h.

12. A lithium ion adsorbing material obtained by the preparation method according to any one of claims 6 to 11.

13. Use of the lithium ion adsorbing material according to any one of claims 1 to 5 and 12 in lithium extraction, preferably in lithium extraction in a liquid environment.

Citation Information

Patent Citations

  • Lithium ion adsorbent as well as preparation method and application thereof

    CN121819782A

  • Diene-copolymer substituted with alkoxy silane, and organicand inoragnic hybrid composition using the substituted diene-compolymer

    KR1020000061084A

  • Lithium ion adsorbents

    US20230241581A1

  • Compositions and methods for selective extraction of lithium

    WO2023081448A1